Kultur Masyarakat Melayu: Studi Etnografi Islam Melayu Nusantara Abad 18 - Kuswandi, Dedi; Rusli, Ris’an; Sani, Amilda (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Today, Malay is not an ethnic community as understood by many people. Malays are like a nation or group of allied ethnic groups that adhere to the same religion and the same language. Customs and traditions are relatively the same because they are based on the same religious and cultural principles. Therefore, the purpose of this research is to examine how the development of Malay Islam in the archipelago in the 18th century. This study uses a qualitative approach with ethnographic methods where researchers will describe and describe the culture of the development of Islam in the archipelago through the history that has been communicated. Tracing the history of the development of Islam in the Malay Archipelago, it emerged due to many factors, starting with trade in the 8th and 9th centuries until finally the 17th century, trade took place accompanied by the development of Islam which was also rife. However, in the 18th century, Islam developed rapidly and began to emphasize sharia. So, it greatly impacts the development of tariqat and experiences a renewal of Sufi tariqat, which grows into a religious organization. Not only that, in the 18th century the role of the clergy was significant in the spread of Islam after the return of the clergy learned from the lands of Mecca and Medina. Establishing Islamic educational institutions throughout the archipelago and providing new religious ideas in carrying out worship. Therefore, in this century, Islam began to form intellectual networks or scholars throughout the archipelago. Islam and the Malay language then emerged as an integrative force for the different ethnic groups in the archipelago.